Accounting, Finance and Digital Marketing Education for Business Groups: A Study in Kuala Lumpur, Malaysia - Ibrahim, Fifi Nurafifah; Sutiawati, Sutiawati; Rosmawati, Rosmawati; Muslim, Muslim (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: The purpose of this study is to explore the importance of effective financial record management practices and efficient marketing techniques for Micro, Small, and Medium Enterprises (MSMEs) in escalating corporate competition. Study design/methodology/approach: This study adopts an exploratory approach to examine the role of accounting as a methodical process encompassing the recording, classification, consolidation, manipulation, and communication of financial information, transactions, and events. It also explores how integrating technology can amplify product marketing endeavors for MSMEs. Findings: The study finds that adopting effective financial record management practices and efficient marketing techniques is crucial for MSMEs in today's competitive business environment. Accounting serves as an essential instrument in aiding financial planning and administration, while the integration of technology facilitates broader outreach to a more comprehensive demographic of consumers. Originality/value: This study highlights the importance of financial record management and marketing for MSMEs and provides insights into how accounting and technology can contribute to their success. The study also emphasizes the significance of providing educational resources, advisory services, and assistance in accounting, finance, and digital marketing to help individuals gain knowledge and improve their financial and marketing skills.